The Association of Acute Kidney Injury with the Development and Progression of Chronic Kidney Disease: A Systematic Review - Adzana Yasadhy Hangga Prasetyo (International Medical Journal Corp. Ltd, 2025)
Background: The incidence of acute kidney injury (AKI) is rising globally, representing a significant burden on healthcare systems. Historically considered a transient and fully reversible condition, a substantial body of evidence now suggests that an episode of AKI is a major independent risk factor for adverse long-term sequelae, most notably the development and progression of chronic kidney disease (CKD). This systematic review aims to synthesize and critically appraise the current evidence from observational cohort studies to quantify the long-term risks associated with AKI. Methods: A systematic search of the PubMed and Embase databases was conducted to identify cohort studies published from inception to September 2025 that evaluated long-term outcomes in adult patients following an episode of AKI, with a non-AKI comparator group. Studies were selected based on predefined Population, Intervention/Exposure, Comparison, Outcomes, and Study Design (PICOS) criteria, requiring a minimum follow-up of one year. Data on study design, population characteristics, definitions of AKI and CKD, follow-up duration, and reported outcomes were systematically extracted. The methodological quality and risk of bias for each included study were assessed using the Newcastle-Ottawa Scale (NOS). Results: Seventeen cohort studies, encompassing a total of 2,546,812 participants, met the inclusion criteria. The evidence consistently demonstrated that patients who survive an episode of AKI have a significantly higher risk of adverse long-term outcomes compared to those without AKI. The pooled adjusted Hazard Ratio (HR) for developing incident CKD was 2.72 (95% CI 2.01–3.69). The risk for progressing to end-stage renal disease (ESRD) was even more pronounced, with a pooled adjusted HR of 4.15 (95% CI 2.58–6.67). Furthermore, AKI was associated with a nearly doubled risk of long-term all-cause mortality (pooled adjusted HR 1.85, 95% CI 1.65–2.08). The risk for all outcomes was graded, increasing with the severity and duration of the initial AKI episode. Notably, even mild (Stage 1) or transient (<3 days) AKI was associated with a significantly increased risk of incident CKD. Other significant adverse outcomes included increased risks of heart failure, myocardial infarction, and recurrent AKI. Discussion: The synthesized evidence robustly demonstrates that AKI is not merely a transient event but a sentinel insult that can initiate a persistent trajectory toward chronic disease and premature death. The pathophysiological transition from AKI to CKD is driven by complex processes of maladaptive repair, including persistent inflammation, endothelial dysfunction, cellular senescence, and ultimately, renal fibrosis. These findings challenge the conventional clinical paradigm of